Autobiographical notes in "Once More to the Lake" - Acharya, Dhiraj (The Journal of Knowledge and Innovation, 2023)
This paper depicts “Once More to the Lake” is related to autobiographical theme. Autobiographical memory is taken as the main problem of this research paper. For the analysis of this paper memory, experience and feelings about nature has been presented as research questions. This research is related to library work. It is applied on the basis of qualitative methodology and text based explanatory method. This paper is based on autobiographical narrative theory. Autobiographical narrative transparently explore the constitutive process of autobiographical subjectivity. They are: memory, experience, identity, agency and embodiment. This paper discuss about narrator’s experience of visiting to lake with his father and narrator revisiting the same lake with his son and reminds him about his past experience. It reflects about the natural environment of the lake and it shows the relationship between nature organism and human beings. It shows how fragments of experience change over time and those experience reminds about the individual life.